PENERAPAN STRATEGI SELF MANAGEMENT UNTUK MENGURANGI KETERLAMBATAN SISWA SMA NEGERI 1 PLAOSAN TAHUN PELAJARAN 2019/2020 - Sumber Wanitun (Dwija Inspira: Jurnal Pendidikan Multi Perspektif, 2020)
This study aims to reduce student tardiness by using self-management strategies. This shows that many students do not arrive on time. For this reason, the data is taken from the late events that occurred and then coached with a self-management strategy. From the data per cycle, it was found that each cycle of students experienced a decrease in tardiness. With the self-management strategy, student delays can be better reduced.